Effects of atmospheres on sulfur release and its transformation behavior during coal thermolysis. (1st March 2018) - Yang, Nuannuan; Guo, Huiqing; Liu, Fenrong; Zhang, Hao; Hu, Yongfeng; Hu, Ruisheng
Abstract: In this study, Pinshuo (PS) coal with high organic sulfur content was selected to investigate the effects of atmospheres on sulfur release and its transformation during thermolysis. Pyrolysis connected with gas chromatography (Py-GC) was used to analyze the sulfur containing gases of H2 S, COS and SO2 . Sulfur K-edge XANES was carried out to study the sulfur transformation after thermolysis. For PS raw, deashed and depyrited coals, the order of effect of atmospheres on sulfur removal is 3% O2 -Ar > CO2  > 85% CO2 -Ar > 75% CO2 -Ar > Ar. The trends about the effects of 3% O2 -Ar atmosphere on sulfur removal and char yield are similar to CO2 atmosphere, but desulfurization rate is slightly higher under 3% O2 -Ar atmosphere than that under CO2 atmosphere, while the char yield is much lower under 3% O2 -Ar than that under CO2 . This indicates that CO2 atmosphere is a moderate atmosphere for sulfur removal. SO2 release concentration, its maximum peak temperature and its release amount is the highest under 3% O2 -Ar atmosphere. Meanwhile, most of sulfurs in the gas phase is SO2 under 3% O2 -Ar atmosphere and H2 S under 85% CO2 -Ar, 75% CO2 -Ar and Ar. However, H2 S, COS and SO2 are all relatively high under pure CO2 atmosphere. Based on the analysis of sulfur K-edge XANES, more thiophenes are easily gathered in the chars after thermolysis under those atmospheres. Thiophenes peak in the char under 3% O2 - Ar atmosphere are lower than other atmospheres, which indicates some stable thiophenes are relatively easier to decompose under this atmosphere. This is also in agreement with the higher sulfur removal under 3% O2 - Ar atmosphere. According to the similar XANES spectra of thiophenes, the effects of those three CO2 atmospheres on sulfur transformation in the chars are almost the same, but desulfurization rate is the highest under pure CO2 atmosphere.